A società Dante Alighieri: um estudo de caso sobre o associativismo étnico italiano em São Carlos/SP – 1902 a 1938 - Conceição, Carla Fernandes da (2020)
The present PhD thesis has the objective of analyzing the associationism practice by the Italian immigrants in the São Carlos, São Paulo State, in the years of 1902 through 1938, by understanding the activities of “Dante Alighieri” Italian Society. With this aim, the study is based on comprehending the society as a social space in which the Italian immigrant builds its ethnic identity, associating the mechanisms and strategies of incorporation to the host society upon its professional, economical, cultural, educational and social capitals. The director members of the society, president and vice-president will have a focus in the present study, based on the analysis of regional, professional, educational trajectories, in relation to the fascism and the construction of individual and associativist trajectories. The source of the study is based on several documents, mainly on minutes from ordinary meetings and board meetings of the studied society, complemented by the analysis of the articles of incorporation of the society, as well as local newspapers at the time, city Almanac, in the Municipal census of 1907, marriage certificates, books, journal articles, thesis and dissertations. The present research then prioritizes a qualitative analysis but does not disregard the use of qualitative documents. In the end, the present study will contribute to understand the associationism practices of Italian immigrants in São Carlos, by using the Dante Alighieri Italian Society as a case study, which so far has been a theme not well covered in the literature.